Flexible power generation scenarios for biogas plants operated in Germany: impacts on economic viability and GHG emissions. (20th July 2016) - Lauer, Markus; Dotzauer, Martin; Hennig, Christiane; Lehmann, Monique; Nebel, Eva; Postel, Jan; Szarka, Nora; Thrän, Daniela
Summary: Biogas plants enable power to be generated in a flexible way so that variable, renewable energy sources can be integrated into the energy system. In Germany, the Renewable Energy Sources Act promotes flexible power generation in biogas plants. Two existing biogas plants in flexible operation were analyzed with respect to economic viability and greenhouse gas (GHG) emissions to assess the feasibility of flexible operation. To do this, a biogas technology simulation model was developed to reproduce the technical design of both biogas plants and to link this design with twelve flexibilization scenarios. The evaluation of the economic viability is based on a discounting method of investment appraisal. For assessing the level of GHG emissions, the life cycle assessment method has been applied. The results show that the profitability of flexibilization is contingent upon premium payments promoting flexibility and direct sales resulting from a higher electrical efficiency of new or additionally installed combined heat and power units. Overall, with respect to profitability, the results of the flexible power generation scenarios are dependent upon the properties of the technical plant, such as its power generation and gas storage capacities. Relative GHG emissions from flexible biogas plants show significantly lower values than for referenced fossil gas–steam power stations. Among the various scenarios, the results reveal that the level of GHG emissions especially depends on the number of operating hours of the additional combined heat and power unit(s). The results of the analyzed biogas plants showed no direct correlation between GHG emissions and the economic benefits. Overall, a flexible power generation of biogas plants may improve the economic viability as well as result in lower GHG emissions in comparison with a conventional base load operation. © 2016 The Authors. International Journal of Energy Research published by John Wiley & Sons Ltd. Abstract : Biogas plants, especially those with large gas storage capacities, heat sinks and no temporal limitation of the heat supply, can economically benefit from flexible power generation. The current incentive scheme promotes investment, especially combined heat and power units, and/or additional gas storage capacities. Relative greenhouse gas emissions from flexible biogas plants are significantly lower than from gas‐steam power stations.